1994
DOI: 10.1111/j.1528-1157.1994.tb02481.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Epilepsy and Asthma: Comparison of Quality of Life

Abstract: We report results from the first data collection on an ongoing longitudinal study aimed at describing the natural history of adaptation to childhood epilepsy and asthma in children and their families. We studied 136 children with epilepsy and 134 children with asthma aged 8-12 years. Data were collected from the children, their mothers, and their school teachers through interviews, school records, and questionnaires. The two samples were compared on four domains of quality of life: physical, psychological, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
89
0
10

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 185 publications
(107 citation statements)
references
References 30 publications
8
89
0
10
Order By: Relevance
“…Obviously, there is a very important role for the CBCL in the broad-based assessment of childhood behavior and it has been frequently used in the pediatric epilepsy literature. 1,21 Nevertheless, the BRIEF appears to be a worthwhile complement by providing a standardized parent-report measure of EF.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, there is a very important role for the CBCL in the broad-based assessment of childhood behavior and it has been frequently used in the pediatric epilepsy literature. 1,21 Nevertheless, the BRIEF appears to be a worthwhile complement by providing a standardized parent-report measure of EF.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Norrby et al (24) found that children with controlled epilepsy and no obvious neurodeficits did not differ from aged-matched controls when describing themselves using 39 bipolar adjectives and a VAS of well-being. Austin et al (25), Hoare and Kerley (26), and Carpay et al (27) addressed selected concerns of children with epilepsy, such as relationships with siblings, stigma, self-esteem, and restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on child attitudes because children with more negative attitudes toward having epilepsy had been found to have poorer adjustment in past research (Austin et al, 1994;LeBovidge et al, 2005). We considered attitude toward the condition to be an important influence on adjustment and developed a preliminary model with concepts that might be predictors of child attitude.…”
Section: Discussionmentioning
confidence: 99%
“…Our past research has suggested that children's attitudes toward having epilepsy might influence their psychosocial adjustment. For example, we found more positive attitudes toward epilepsy to be associated with more positive selfconcepts (Austin & Huberty, 1993), greater use of adaptive coping strategies (Austin, Patterson, & Huberty, 1991), and fewer behavior problems (Austin, Smith, Risinger, & McNelis, 1994). Child attitude toward illness was conceptualized as an important influence on adjustment in a recent study of children with chronic arthritis (LeBovidge, Lavigne, & Miller, 2005).…”
mentioning
confidence: 99%